2006
DOI: 10.1681/asn.2005101095
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Renal Response to Renin-Angiotensin System Blockade

Abstract: Evidence suggests that gender differences exist in renin-angiotensin system (RAS) function. It was hypothesized that women may differ also in their response to RAS blockade. The renal and peripheral hemodynamic responses to incremental dosages of an angiotensin receptor blocker and the degree of angiotensin II (AngII) insensitivity achieved during 8 wk were examined in men and women. Participants were 30 young healthy men (n ‫؍‬ 15; mean age 27 ؎ 2) and women (n ‫؍‬ 15; mean age 28 ؎ 2) who were on a controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 26 publications
9
109
2
Order By: Relevance
“…35 It has been speculated that activation of the AT 2 R or NO or both could be mediating these effects. 34,35 Our results are consistent with such a conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…35 It has been speculated that activation of the AT 2 R or NO or both could be mediating these effects. 34,35 Our results are consistent with such a conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…In a study performed by Miller et al 33 that examined the renal response of young healthy subjects to graded Ang II infusion, GFR was maintained in men, whereas in women GFR declined. More recently, Miller et al 34 demonstrated that in the presence of AT 1 R blockade, women exhibited a significantly blunted RBF response to Ang II compared to men. Sexual dimorphism in the nonmodulation phenotype of hypertension, 35 which is characterized by a lowered RBF response to Ang II with a high-salt diet, also has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of the AT 2 R receptor has been associated with hypertension in premenopausal women but not in men. 30 Furthermore, on a background of AT 1 R blockade, the renal response to Ang II infusion was attenuated more in women than in men, suggesting a role for the AT 2 R. 31 Supporting these findings, we found that the female WT mice had a 3-fold higher basal AT 2 R expression compared with males ( Figure 3). Importantly, in the current study, basal mRNA expression levels of the AT 1a R and the AT 1b R were not different between the males and females and increased by the same magnitude in response to Ang II and, thus, do not seem to contribute to the attenuated pressor response to Ang II in the WT females.…”
Section: Brown Et Al At 2 R and Sex-dependent Ang II Responsesupporting
confidence: 69%
“…These previous observational studies are consistent with our findings, since SBP was higher and DBP lower in the two youngest groups of DM vs. control subjects. Although our study did not define the mechanisms responsible for exaggerated ANG II responses in older diabetic subjects, the augmented response may have been due to ANG II type 1 receptor upregulation, which can increase ANG II sensitivity in humans (14,21). AT 1 receptor upregulation, which has been observed in aging human vascular tissue, may have been due to the observed declines in circulating RAS mediators or to DM-related increased AT 1 receptor mRNA expression and signaling (14,31,32).…”
Section: Discussionmentioning
confidence: 74%
“…Between group differences in renal hemodynamic responses to hyperglycemia and ANG II were determined by repeated measures ANOVA. We controlled for baseline between group differences in hemodynamic parameters by entering these factors into a multivariate stepwise regression analysis, and we controlled for the effects of gender and body mass index (BMI) on renal function by including these factors in the statistical model (21,(27)(28)(29). In the primary analysis, we included the entire 66 member cohort and did not correct for differences in diabetes duration.…”
Section: Subjectsmentioning
confidence: 99%